Satellite-based Determination and Analysis of Groundwater Drought Index Time Series in Europe - Biryło, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
According to the European Drought Observatory, more than 30% of Europe has been under drought warning conditions since 2018. This situation is primarily attributed to a persistent decline in groundwater resources. Satellite observations confirm that groundwater levels have not been recovering; in some regions, they continue to decrease. Data from the Global Gravity-based Groundwater Product (G3P) project, which employs satellite gravimetric measurements, enable continuous monitoring of groundwater variations and provide a globally consistent map of gravity field changes, directly converted into terrestrial water storage variations, of which groundwater is a key component.
Keywords: groundwater; drought; Europe; climate; Fourier transform; GRACE; G3P; time series decomposition